Increased BUN and glucose in a group of San Cristóbal galapagos tortoises (Chelonoidis chathamensis). Issue 2 (2nd May 2019) - Cerreta, Anthony J.; Vaden, Shelly L.; Lewbart, Gregory A.; Muñoz‐Pérez, Juan Pablo; Páez‐Rosas, Diego
Abstract : Veterinary health examinations were performed on 19 captive tortoises in seminatural conditions at the 'Galapaguera of Cerro Colorado' and at the 'Otoy Ranch' on San Cristóbal Island, Galápagos. No abnormalities were found during physical examination, but there were significant increases in glucose and blood urea nitrogen concentrations in the tortoises sampled at the Otoy Ranch (p = 0.001 and p < 0.001, respectively). The glucose concentration in tortoises at the Otoy Ranch was also increased compared with health assessments conducted 1 year previously. It is suspected that diet is responsible for these differences, due to the fact that in the wild, Galapagos tortoises consume large quantities of low energy forage and previous studies have correlated a captive diet with excess dietary protein to a shortened life expectancy. These peripheral blood chemistry abnormalities constitute a need for future research in the nutrition of the Galapagos tortoise to help ensure the health and survival of these species.